Monitoring Progress towards Universal Health Coverage at Country and Global Levels - Boerma, Ties; Eozenou, Patrick; Evans, David; Evans, Tim; Kieny, Marie-Paule; Wagstaff, Adam (Public Library of Science, 2016)
Universal health coverage (UHC) has been defined as the desired outcome of health system performance whereby all people who need health services (promotion, prevention, treatment, rehabilitation, and palliation) receive them, without undue financial hardship. UHC has two interrelated components: the full spectrum of good-quality, essential health services according to need, and protection from financial hardship, including possible impoverishment, due to out-of-pocket payments for health services. Both components should benefit the entire population.